A tale of 10 European centres - 2010 APOSSM travelling fellowship review in ACL surgery - Lee Yee Han; Kuroda Ryosuke; Zhao Jinzhong; Chan Kai (BMC, 2012)
Abstract The purpose of ESSKA- APOSSM Travelling fellowship is to better understand the epidemiology, management and surgical techniques for sports across continents. There has been a progressive evolution in ACL reconstruction and there is variation in technique in ACL reconstruction amongst the most experienced surgeons in different continents. During this one month fellowship, we saw various ACL reconstruction techniques using different graft sources, with a variety of graft fixation methods, with the common aim of recreating an anatomical ACL reconstruction.